2016
DOI: 10.4049/jimmunol.1601198
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: BAFF Overexpression Reduces Atherosclerosis via TACI-Dependent B Cell Activation

Abstract: Patients with SLE exhibit accelerated atherosclerosis, a chronic inflammatory disease of the arterial wall. The impact of B cells in atherosclerosis is controversial, with both protective and pathogenic roles described. For example, natural IgM binding conserved oxidized lipid epitopes protect against atherosclerosis, while anti-oxidized low-density lipoprotein (oxLDL) IgG likely promotes disease. Since B cell activating factor of the TNF family (BAFF) promotes B cell class-switch recombination and humoral aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…Furthermore, there may be additional mechanisms through increased plasma BAFF levels, as a result of B cell deficiency. BAFF, a critical survival factor for B cells, has anti-inflammatory effects as BAFF overexpression or neutralization reduced atherosclerosis (47,48). In addition to BAFF Receptor (BAFFR), BAFF also interacts with B cell maturation antigen (BCMA), and TNFR homolog transmembrane activator and Ca 2+ modulator and CAML interactor (TACI).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there may be additional mechanisms through increased plasma BAFF levels, as a result of B cell deficiency. BAFF, a critical survival factor for B cells, has anti-inflammatory effects as BAFF overexpression or neutralization reduced atherosclerosis (47,48). In addition to BAFF Receptor (BAFFR), BAFF also interacts with B cell maturation antigen (BCMA), and TNFR homolog transmembrane activator and Ca 2+ modulator and CAML interactor (TACI).…”
Section: Discussionmentioning
confidence: 99%
“…Interaction of BAFF with BAFF-R on immature B cells promotes their differentiation into the transitional stage, and immature B cells with minimal BAFF-R levels have been associated with an autoreactive phenotype (48). In accord, decreased Baff-R expression as observed in Mifdeficient B cells may favor BAFF signaling over its lower affinity receptor TACI, which has been shown to increase autoantibody titers against modified LDL in atherosclerosis (49). Moreover, pan B cells in Mif 2/2 Apoe 2/2 BM showed an increased expression of Bcl-2, which has been associated with delayed elimination of self-reactive B cells (33).…”
Section: Discussionmentioning
confidence: 99%
“…135,136 In murine arthritis, BAFF-silenced synovial dendritic cells remained immature and were unable to support T-helper type 17 (Th17) differentiation. 141,142 Mechanistically, BAFF-dependent TACI signals in atheroma M1 macrophages decreased the production of the pro-atherogenic chemokine CXCL10, resulting in accelerated atherosclerosis after global and myeloid-specific TACI deletion. For example, an intriguing new study showed that TACI-dependent production of the regulatory cytokine IL-10 by IgA + plasma cells protected against experimental autoimmune encephalomyelitis (EAE) in BAFF-Tg mice.…”
Section: Other Effec Ts Of Baff Inhib Iti On On Infl Ammationmentioning
confidence: 99%
“…Similarly, whereas global and B cellspecific BAFF-R deletion protected against atherosclerosis, BAFF neutralization increased and BAFF overexpression limited atheroma formation in mouse models. 141,142 Mechanistically, BAFF-dependent TACI signals in atheroma M1 macrophages decreased the production of the pro-atherogenic chemokine CXCL10, resulting in accelerated atherosclerosis after global and myeloid-specific TACI deletion. 141 Since elevated serum BAFF levels are associated with increased atherosclerosis risk in human SLE, 143 the clinical relevance of these animal models to human lupus is unclear.…”
Section: Other Effec Ts Of Baff Inhib Iti On On Infl Ammationmentioning
confidence: 99%